Penguatan Kapasitas Kewirausahaan untuk Mendorong Inovasi Berbasis Pemanfaatan Lingkungan pada Peserta Didik di SMK Triguna Utama - Hamda, Nasmal; Erda Tarsia, Fanni; Nurhasanah, Enok (Universitas Pamulang, 2026)
This Community Service Program (PKM) aims to enhance students’ entrepreneurial capacity through innovation based on the utilization of the environment at SMK Triguna Utama. The program is motivated by students’ low skills in developing creative business ideas and the suboptimal use of the surrounding school environment as a source of product innovation. The PKM implementation methods included socialization, interactive training, hands-on practice, and outcome evaluation. Students were trained to identify business opportunities from waste materials, design creative products, and understand the basics of simple business management. The results showed that students were able to produce various recycled products, such as crafts made from plastic bottles and used paper that have market value. In addition, the activities fostered entrepreneurial motivation, increased creativity, and built awareness of the importance of environmental conservation. Overall, this PKM activity had a positive impact on improving students’ entrepreneurial knowledge, skills, and attitudes. The program serves as tangible evidence of synergy between higher education institutions and vocational high schools in supporting environmentally based entrepreneurship education. Keywords: entrepreneurship, innovation, environmental utilization, students, SMK Triguna Utama